Hybrid sterility in the mouse - Forejt, J (Trends in genetics, 1996)
The sterility of hybrids between various mouse species follows Haldane's rule by affecting only the males. Hitherto, five hybrid sterility (Hst) loci have been identified in the mouse genome. Haldane's rule holds also for chromosomal sterility in all studied mammalian species, including man. The males heterozygous for various male-sterile chromosomal rearrangements show the same meiotic phenotype: partially asynaptic, rearranged autosomes associate with the X Chromosome. Thus, the X-Chromosome inactivation in the male meiosis might function as a checkpoint leading to the meiotic arrest in sterile hybrids. Chromosomal and gene hybrid sterility might be interrelated because the attributes of chromosomal sterility, such as X-autosome associations, occur also in interspecies hybrids with genic sterility.
Keywords: Fertility; Male; Chromosome Mapping; Infertility, Male; spermatogeneze; Meiosis; Spermatogenesis; mužské pohlaví; Models, Genetic; chromozom X; Muridae; X Chromosome; fertilita; meióza; Animals; lidé; ženské pohlaví; mapování chromozomů; Humans; zvířata; modely genetické; Hybridization, Genetic; myši; hybridizace genetická; Mice; Female; mužská infertilita